Effect of Intra-operative Intra-arterial Thrombolysis on Long Term Clinical Outcomes in Patients with Acute Popliteal Artery Aneurysm Thrombosis. (February 2020) - Dragas, Marko; Zlatanovic, Petar; Koncar, Igor; Ilic, Nikola; Radmili, Oliver; Savic, Nebojsa; Markovic, Miroslav; Davidovic, Lazar
Abstract : Objective: Acute lower limb ischaemia (ALI) as a result of popliteal artery aneurysm (PAA) thrombosis represents a significant problem. The aim of this study was to investigate outcome of intra-operative intra-arterial thrombolysis in the treatment of acute ischaemia due to PAA thrombosis in terms of major adverse limb events (MALE), overall survival, and intrahospital complications, especially those associated with bleeding. Methods: A total of 156 patients with Rutherford grade IIa and IIb acute ischaemia resulting from PAA thrombosis were admitted between 1 January 2011 and 1 January 2017. The patients were divided into two groups, those who underwent additional treatment with intra-operative intra-arterial thrombolysis (20 patients), and those who did not (136 patients). By using covariables from baseline and angiographic characteristics, a propensity score was calculated for each patient. Each patient who underwent intra-operative thrombolysis was matched to four patients from the non-thrombolysis group. Thus, comparable patient cohorts (20 in the thrombolysis and 80 in the non-thrombolysis group) were identified for further analysis. The primary end point was MALE and the secondary endpoint all cause mortality. Results: After a median follow up of 55 months, the estimated MALE rate was significantly lower in the thrombolysis group (30% vs. 65%, chi square = 10.86, p <  .001, log rank test). Also, patients in the thrombolysis group had a significantly lower mortality rate (20% vs. 42.65%, chi square = 3.65, p =  .05, log rank test). The thrombolysis group had wound/haematoma related interventions performed more commonly (25% in thrombolysis vs 8%, in non-thrombolysis group), but the difference was not significant (p=.013). There were no cases of major (intracranial and gastrointestinal) bleeding in either group. Conclusion: The data suggest that intra-operative thrombolysis in the treatment of selected patients with ALI due to PAA thrombosis has long term MALE and overall survival benefits, without a significant risk of major, life threatening bleeding complications.